(untitled) (Communications in Computational Physics, 2020)
Fresh water is one of the most significant resources for human activities and survival, and irrigation is among the most important uses of water. The sustainibility and performance of irrigation canals can be greatly affected by sediment transport and deposition. In our previous works, we proposed a Lattice Boltzmann model for simulating a free surface flow in an irrigation canal, as an alternative to more traditional models mainly based on shallow water equations. Here we introduce the sedimentation phenomenon into our model by adding a new algorithm, based on the earlier work by B. Chopard, A. Dupuis and A. Masselot [9, 11, 12, 27]. Transport, erosion, deposition and toppling of sediments are taken into account and enable the global sedimentation algorithm to simulate different transport modes such as bed load and suspended load. In the present work, we study both the behaviour of a sediment deposit located at an underflow submerged gate (depending on the gate opening and the flow discharge) and the influence of the presence of such a deposit on the flow. Both numerical and experimental validations have been performed. The experiments were realized on the micro-canal of the LCIS laboratory at Valence, France. The comparisons between simulations and experiments give good qualitative agreement.